2015
DOI: 10.1089/mab.2015.0013
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Murine Monoclonal Antibodies anti-PBP2a of Methicillin-resistantStaphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a multidrug-resistant bacterium that causes serious infections worldwide. This pathogen is resistant to all beta lactam antibiotics due the presence of PBP2a, a transpeptidase enzyme that presents very low beta-lactam affinity. Here we report the generation and characterization of mouse monoclonal antibodies to PBP2a of MRSA strains. Two clones were obtained and characterized by immunoassays (ELISA, avidity index determination, and immunoblotting), isotypin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…aureus [11], confirming the specificity of anti-PBP2a antibodies against MRSA. The MAb presented here was derived from this work, and it was obtained and characterized in previous studies [11,13,14]. We previously demonstrated that this MAb binds strongly to recombinant PBP2a and recognizes native PBP2a protein on the bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus [11], confirming the specificity of anti-PBP2a antibodies against MRSA. The MAb presented here was derived from this work, and it was obtained and characterized in previous studies [11,13,14]. We previously demonstrated that this MAb binds strongly to recombinant PBP2a and recognizes native PBP2a protein on the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies employing DNA vaccination demonstrated that PBP2a generates an immune response and eliminates bacteria after systemic infection in immunized mice [1112]. We recently reported the generation and characterization of murine MAbs that specifically bind PBP2a in vitro with high affinity [13]. In another study, we demonstrated that this anti-PBP2a antibody recognizes PBP2a protein on the bacterial surface using an immunofluorescence assay [14].…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained by Naghshbandi et al showed that passive immunization with rabbit purified polyclonal antibodies against recombinant PBP2a results in a significant increase in the survival rate of mice challenged with a lethal dose of MRSA and reduction of bacterial spread to the internal organs, confirming the potential importance of passive immunization with anti-PBP2a antibodies in controlling MRSA infections [ 81 ]. Monoclonal antibodies against PBP2a have also been generated and extensively characterized, but their efficacy in immunoprophylaxisis is still to be determined [ 82 , 83 ].…”
Section: Antibodies In Bacterial Infectionsmentioning
confidence: 99%
“…[ 12 ] This causes the bacteria to lose resistance to beta‐lactam antibiotics because their cell walls can no longer effectively remain intact, ultimately leading to the death of the bacterium. [ 13 ] By blocking the function of PBP2a, anti‐PBP2a can inhibit the proliferation of MRSA and other PBP2a‐carrying bacteria.…”
Section: Introductionmentioning
confidence: 99%